Enhancing adolescent well-being in the digital age: exploring the interplay of parental and peer relationships with gender as a moderating variabel - Aulia, Farah; Utami, Rahayu Hardianti; Magistarina, Elrisfa; Kurniawan, Rizal; Setiawan, M. Yasep; Ade, Frihapma Semita; Purna, Rozi Sastra; Hasanah, Afifah Nur; Khasanah, Andhita Nurul (Jurnal Konseling dan Pendidikan, 2025)
The internet has become essential to people of all ages, particularly teenagers, to access information, education, and entertainment. Studying adolescents' well-being has become a hot topic lately, with digital technology and the internet as part of everyday life. The purpose of this study is to examine the role of gender in moderating the relationship between parental and peer relationships with adolescent well-being. Participants in this study were 749 internet user adolescents from various regions in Indonesia, who were selected using convenient sampling techniques. Data was collected online using the EPOCH measure for adolescent well-being, parent-adolescent relationship scales, and friendship quality scales. The results of the hierarchical linear modelling indicate that there is a positive correlation between parent and peer relationships, and adolescent well-being. The findings indicate that the relationship between the two variables is more pronounced among the male population than the female population.